Female fertility does not require Bmal1 in suprachiasmatic nucleus neurons expressing arginine vasopressin, vasoactive intestinal peptide, or neuromedin-S - Tonsfeldt, Karen J.; Cui, Laura J.; Lee, Jinkwon; Walbeek, Thijs J.; Brusman, Liza E.; Jin, Ye; Mieda, Michihiro; Gorman, Michael R.; Mellon, Pamela L. (Frontiers in Endocrinology, 2022)
Disruptions to the circadian system alter reproductive capacity, particularly in females. Mice lacking the core circadian clock gene, Bmal1, are infertile and have evidence of neuroendocrine disruption including the absence of the preovulatory luteinizing hormone (LH) surge and enhanced responsiveness to exogenous kisspeptin. Here, we explore the role of Bmal1 in suprachiasmatic nucleus (SCN) neuron populations known to project to the neuroendocrine axis. We generated four mouse lines using Cre/Lox technology to create conditional deletion of Bmal1 in arginine vasopressin (Bmal1fl/fl:Avpcre), vasoactive intestinal peptide (Bmal1fl/fl:Vipcre), both (Bmal1fl/fl:Avpcre+Vipcre), and neuromedin-s (Bmal1fl/fl:Nmscre) neurons. We demonstrate that the loss of Bmal1 in these populations has substantial effects on home-cage circadian activity and temperature rhythms. Despite this, we found that female mice from these lines demonstrated normal estrus cycles, fecundity, kisspeptin responsiveness, and inducible LH surge. We found no evidence of reproductive disruption in constant darkness. Overall, our results indicate that while conditional Bmal1 knockout in AVP, VIP, or NMS neurons is sufficient to disrupted locomotor activity, this disruption is insufficient to recapitulate the neuroendocrine reproductive effects of the whole-body Bmal1 knockout.